2015
DOI: 10.1136/bjophthalmol-2015-306641
|View full text |Cite
|
Sign up to set email alerts
|

Corneal inlay implantation complicated by infectious keratitis

Abstract: Infectious keratitis can occur at an early or late stage following corneal inlay implantation. Final visual acuity can be limited by stromal scarring; in the cases where the infiltrate was small and off the visual axis at the time of presentation, the final visual acuity was better than those patients who presented with larger lesions affecting the visual axis. Though infection may necessitate removal of the inlay, early positive response to treatment may enable the inlay to be left in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The healing response is a major risk of an adverse outcome with possible stromal thickening over the inlay causing a hyperopic shift from the flattened overlying epithelium [28]. Other adverse events have been reported such as corneal haze, epithelial iron deposition, and infectious keratitis [48, 49]. Unwanted outcomes can be handled by removing the inlay.…”
Section: Kamra Small Aperture Inlaymentioning
confidence: 99%
“…The healing response is a major risk of an adverse outcome with possible stromal thickening over the inlay causing a hyperopic shift from the flattened overlying epithelium [28]. Other adverse events have been reported such as corneal haze, epithelial iron deposition, and infectious keratitis [48, 49]. Unwanted outcomes can be handled by removing the inlay.…”
Section: Kamra Small Aperture Inlaymentioning
confidence: 99%
“…When the inlay is removed, the patient’s visual acuity returns to ranges comparable to the preoperative state 11,15,16. In the FDA clinical trials, 15 (3%) patients had their inlay removed at 12 months, 36 (7%) at 24 months, and 44 (8%) at 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction after KAMRA inlay has been evaluated by several studies and has been shown to be good 7,9,11,17. Patient satisfaction from the FDA clinical trials was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of 5 eyes, patients presented from 6 days to 4 months postoperatively. 37 All patients responded to broad-spectrum fortified topical antibiotics; however, all patients lost corrected vision. At last follow-up, 2 inlays were explanted and 3 remained in situ.…”
Section: ' Postoperative Complicationsmentioning
confidence: 99%